Analisis Yurudis Proses Penyidikan Tindak Pidana Kekerasan Seksual Menurut Hukum di Indonesia: Analisis Teori Hukum Positif dan Teori Hukum Responsif - M. Bakti Saleh Silaban; Idham Idham; Erniyanti Erniyanti (Penerbit Goodwood, 2022)
Purpose: The purpose of writing this journal is to find out the legal arrangements for investigating sexual violence criminal offenses according to law in Indonesia, and knowing the obstacles and efforts to investigate criminal acts of sexual violence according to law in Indonesia. Method: The method used is a nomative approach through literature study, and an empirical approach, namely through field research by conducting a series of interviews with respondents and informants to obtain field data. Result: The results showed that, the legal regulation of the investigation of sexual violence criminal offenses according to law in Indonesia, namely the criminal acts set firmly and specifically in the Criminal Act of Sexual Violence and also generally regulated by the Criminal Code, but for the investigation process is not specifically regulated in the law -Criminal Acts of Sexual Violence, therefore the law of the event starts from the investigation process to the determination of the court's decision to be regulated in the Criminal Procedure Code. And juridical analysis The process of implementing criminal acts of sexual violence according to law in Indonesia was initially not effective because there was no appropriate legal umbrella and specifically regulating sexual harassment. Conclusion: With a special enlightened regulation of sexual violence, namely Law Number 12 of 2022 concerning Criminal Acts of Sexual Violence, it is expected to protect the victims and become legal umbrellas or legal standing for the police who will handle cases like this, and the perpetrators can given a more deterrent effect so that these cases are reduced even more prevented to occur.